2020
DOI: 10.26504/bkmnext392
|View full text |Cite
|
Sign up to set email alerts
|

Origin and integration: a study of migrants in the 2016 Irish Census

Abstract: I am very pleased to introduce this study on migrant integration using data from Census 2016. The study has been funded by the Department of Justice and Equality under its Equality and Integration Research Programme with the Economic and Social Research Institute. Integration research such as this is essential to the development of evidence-informed policy on integration. This study -the fourth to be produced under the Research Programme, which commenced in 2017makes an important contribution to what we know a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(65 citation statements)
references
References 28 publications
2
61
0
2
Order By: Relevance
“…In Ireland in 2017-2018, the consistent poverty rate 20 was somewhat higher for non-Irish nationals overall, particularly non-EU nationals, though EU-West and EU-East nationals do not differ in terms of consistent poverty risk from Irish nationals. Non-Irish nationals are not more likely to be deprived 21 overall, though non-EU nationals have a higher deprivation risk (McGinnity et al, 2020a).…”
Section: Vulnerability Of Contracting Covid-19 Among Non-irish Nationmentioning
confidence: 90%
See 1 more Smart Citation
“…In Ireland in 2017-2018, the consistent poverty rate 20 was somewhat higher for non-Irish nationals overall, particularly non-EU nationals, though EU-West and EU-East nationals do not differ in terms of consistent poverty risk from Irish nationals. Non-Irish nationals are not more likely to be deprived 21 overall, though non-EU nationals have a higher deprivation risk (McGinnity et al, 2020a).…”
Section: Vulnerability Of Contracting Covid-19 Among Non-irish Nationmentioning
confidence: 90%
“…The report examines the early impact of COVID-19 in Ireland on non-Irish nationals compared to Irish nationals, using the latest available data. It was produced as part of a programme of research on Integration and Equality, funded by Department of Children, Equality, Disability, Integration and Youth in line with the Migrant Integration Strategy 2017-2020, to complement the Monitoring Report on Integration 2020 (McGinnity et al, 2020a).…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…International research on the labour-market outcomes of naturalised and non-naturalised immigrants has typically found that having the citizenship of the host country is associated with better labour-market outcomes for immigrants (Liebig and Von Haaren, 2011;Hoxhaj et al, 2019). Analysis conducted by McGinnity et al (2020a) on migrants in…”
Section: Objectives and Background To The Studymentioning
confidence: 99%
“…Language skills can facilitate integration to the labour market, as well as to society more generally. Recent research using Census 2016 microdata has shown that immigrants in Ireland with better self-rated English language skills are more likely to be employed and have better jobs when they are employed (McGinnity et al, 2020). Fahey et al (2019), analysing the residential distribution of immigrants in Ireland, find that while there is no evidence that migrants in general are concentrated in disadvantaged areas in Ireland.…”
Section: Language Requirementsmentioning
confidence: 99%
“…Goodman (2010) categorises Ireland's citizenship rules as 'enabling', whereby citizenship is viewed as a mechanism for establishing equal status and rights and therefore enabling, rather than 'rewarding', integration. Similarly, in a review of policies granting access to nationality, MIPEX ranked Ireland 14 out of 38 countries, reporting Ireland's naturalisation requirements and procedure to be 'halfway favourable' (Huddleston et al, 2015 likely to be employed, and when they are employed to have a better job, than those who are not Irish citizens (McGinnity et al, 2020). 211 This suggests that the acquisition of Irish citizenship may facilitate labour market integration though the direction of causality is uncertain.…”
Section: Introduction Of Requirements In Ireland Would Represent a Simentioning
confidence: 99%